Infection prevention, control and management: assessing the knowledge among nurses and student nurses in the Eastern Province of Sri Lanka - Wickramasinghe, Darshana; Ubesekara, Suranga V.G.C.; Lokuhewagama, Darshanie K.; Saranasinghe, Dinusha S.A.P.C.; Arachchige, Sampath P.K.H. (Journal of Nepalese Society of Critical Care Medicine, 2024)
Background and aims: The knowledge of infection control among health-care workers is a crucial factor in the success of infection control pro-grams. This study compares the understanding of infection control and prevention practices among nurses and student nurses in eastern province of Sri Lanka. Methods: We utilized a pre-tested self-administered questionnaire with 25 questions. Descriptive statistics and the independent t-test were used to analyze survey responses and compare scores between groups. Results: Out of 178 responses analyzed 112 were nurses and 66 were student-nurses. The average scores were 44% for nurses and 51% for student-nurses. Both groups had less than 10% knowledge of notifiable diseases in Sri Lanka and medical abbreviations. Knowledge about immunization, vaccines, clinical sample transportation, and MRSA decolonization was under 40% for both groups. Overall knowledge of infection control and prevention practices among nurses was significantly poorer than that of student-nurses (p